On-the-tree fruit bagging: A safe approach for production of quality fruits - SHARMA, R R; SETHI, SHRUTI; ASREY, RAM; SAGAR, V R; BHAN, CHANDER (The Indian Journal of Agricultural Sciences, 2021)
During production, fruits undergo several changes. Fruits are also infested by several insect-pests, diseases and birds which reduce their commercial value and thereby cause a significant reduction in yield, quality and returns. To prevent such losses, scientists have developed several good agricultural practices (GAP) which have become quite popular globally for the production of high quality fruits. Among such practices, on-the-tree fruit bagging has emerged as one of the most effective approaches world-wide recently. In this technique, individual fruit or fruit bunch is covered by a bag while attached to the tree. On-the-tree fruit bagging technique has been reported to have several beneficial effects on fruit colour, texture, incidence of several insect-pests, diseases and quality, as a result, it has become an integral part of production technology of apple, pear, peach, grape and loquat in several developed countries. The desirable benefits of fruit bagging may be due to the type of bag used, date and duration of bagging, the stage of fruit development, the duration of fruit exposure to natural light following bag removal, and/or fruit- and cultivar-specific responses. On-the-tree fruit bagging is a simple, grower and eco-friendly approach which has become an integral part of organic fruit production in some parts of the world yet it has to be popularized in India.